Age Determination in young Keeshound Puppies Using a simple Radiographic Study of the Radius, Ulna and Carpus. - Alvarado Morillo, Manuel (Multiciencias)
Radiographic features in the normal development of the radius, ulna and carpal bones from birth to maturity in medium size dogs are reported in order to have an important tool for determining a dog”™s age from radiographs. Eight (male and female) Keeshounds from the ages of one day to eleven months were studied to determine the normal radiographic development of the radius, ulna and carpal bones.At birth, diaphyses of the radius and ulna are present. The epiphyses and carpal bones are absent radiographically because they are composed of cartilaginous tissue. Two weeks later, ossification centers of the accessory carpal bone and lateral humeral condyle can be seen radiographically. At three weeks of age, the ossification center of the proximal radial epiphysis is barely seen. At one month, the ossification center of the medial humeral condyle is present.At six weeks (1Â½months), the ossification center of the distal ulnar epiphysis is present (21 days later than the distal radial epiphysis). By eight weeks of age (two months), all four epiphyses are radiographically present.At fourteen weeks of age (3.5 months), the distal ulnar epiphysis is completely developed. By twenty weeks (five months), the radius and ulna are approximately the same diameter at the level of the mid diaphysis.